Doing the Time Warp: Strange Temporalities and Musical Theatre, Sarah Taylor Ellis (2022). Issue 1 (3rd April 2023) - Yates, Samuel
Review of: Doing the Time Warp: Strange Temporalities and Musical Theatre, Sarah Taylor Ellis (2022) London: Methuen Drama, 288 pp., ISBN 978-1-35015-172-7, h/bk, 115.00